Relationship between the Land Rent and Agricultural Land Prices in the Czech Republic - František Střeleček; Ladislav Jelínek; Jana Lososová; Radek Zdeněk (Statistika: Statistics and Economy Journal, 2011)
The aim of this article is the evaluation of factors and the importance of their impact on the land rent and landprice. A great share of rented land in the Czech Republic requires an assessment of relationship between the land rent and the price of land. Price of land is primarily influenced by location, size and purpose of use of the purchased land. An average market price of agricultural land regardless its location, size and purpose of theland use showed significant differences year by year. The ratio between the land rent and market price of land referred to as the capitalization rate has been increasing continuously since 2003. The payback period that is reciprocal to the capitalization rate corresponds to the standards of European developed states. An averagegrowth rate of the land rent should not exceed 6 % neither should it lead to a mismatch between the development of the land rent and land prices or to a disproportionate growth of land price.